Elderly patients have similar short term outcomes and five-year survival compared to younger patients after pancreaticoduodenectomy. (September 2017) - Shamali, Awad; De'Ath, Henry D.; Jaber, Bashar; Abuawad, Mahmoud; Barbaro, Salvatore; Hamaday, Zaed; Abu Hilal, Mohammad
Abstract: Background: Outcomes following pancreaticoduodenectomy (PD) in elderly patients in the United Kingdom (UK) remain uncertain. This study aimed to analyse peri-operative outcomes in the elderly, and investigate the impact of age on five-year survival following PD in a UK tertiary centre. Materials and methods: All patients who underwent PD in a single Hepatobiliary and Pancreatic unit in the UK between January 2007 to December 2015 were analysed from a prospectively collected database. Individuals were divided into two groups (Group A <75 years and Group B ≥ 75 years "elderly") and outcomes compared. Results: Five hundred and twenty-four patients were included (Group A n = 422, Group B n = 102). Post-operative cardiac events and peri-operative mortality were higher in the elderly (10.8 vs 3.6%, p = 0.008 and 5.9 vs 1.9%, 0.037, respectively). Multivariate analysis revealed only ASA score (OR 0.279, 95% CI 0.063–1.130), post-pancreatectomy haemorrhage (OR 0.055, 95% CI 0.006–0.518) and pulmonary embolism (OR 0.03, 95% CI 0.00–0.148) as independent risk factors for peri-operative mortality. Age was not (OR 0.978, 95% CI 0.911–1.049). Median survival was 22 months in Group A and 19 months in Group B (p = 0.165). Predictors of five-year survival included vascular resection (OR 0.171, 95% CI 0.053–0.549), positive margin (OR 0.256, 95% CI 0.102–0.641), lympho-vascular invasion (OR 0.392, 95% CI 0.160–0.958) and lymph node ratio (OR 67.381, 95% CI 3.301–1375.586), but not age (OR 1.012, 95% CI 0.972–1.054). Conclusion: Older patients have similar peri-operative outcomes and five-year survival compared to younger counterparts after PD in a UK tertiary centre, and should be considered for surgical resection of pancreatic and periampullary cancers. Highlights: Large single UK centre study examining outcomes after pancreaticoduodenectomy (PD). Comparison between elderly (≥75 years) and younger (<75 years) patients. Study revealed that age was not a risk factor for increased peri-operative mortality. Elderly had comparable outcomes and five-year survival to younger patients after PD. Elderly should be offered PD for resection of pancreatic and periampullary cancers.